2023
DOI: 10.3390/met13071233
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Supercapacitive Behavior of Electroless Ni-B Coatings

Mate Czagany,
Szabolcs Hompoth,
Márk Windisch
et al.

Abstract: Amorphous electroless Ni-B coatings were deposited on steel substrates with different surface morphologies and B contents (6.5–8.64 wt.%) that could be changed by altering the temperature and the composition of the baths. The supercapacitive behavior of the coatings was evaluated by cyclic voltammetry and galvanostatic charge–discharge measurements, and it was found that Ni-B coatings had higher capacitance than pure electroless Ni or the bulk Ni plate. A close relationship was identified between the microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Tanwilaisiri et al [68] found that the capacitance of a 3D printed, activated, carbon-based SC decreased from 182 mF to 32 mF as the scan rate increased from 0.02 to 0.1 V/s. Similarly, a decrease in the capacitance of electroless Ni-B coatings with pseudocapacitive properties from 30.61 to 24.61 mF/cm 2 was observed when increasing the scan rate from 0.01 to 0.1 V/s [69]. The decrease can be attributed to a reduced ion diffusion process as, at lower rates, ionic diffusion has enough time to penetrate the inner pores of the electrode.…”
Section: Cyclic Voltammetrymentioning
confidence: 82%
“…Tanwilaisiri et al [68] found that the capacitance of a 3D printed, activated, carbon-based SC decreased from 182 mF to 32 mF as the scan rate increased from 0.02 to 0.1 V/s. Similarly, a decrease in the capacitance of electroless Ni-B coatings with pseudocapacitive properties from 30.61 to 24.61 mF/cm 2 was observed when increasing the scan rate from 0.01 to 0.1 V/s [69]. The decrease can be attributed to a reduced ion diffusion process as, at lower rates, ionic diffusion has enough time to penetrate the inner pores of the electrode.…”
Section: Cyclic Voltammetrymentioning
confidence: 82%